Virtual Colonoscopy and Abdominal Imaging: Computational Challenges and Clinical Opportunities Second International Workshop, Held in Conjunction with MICCAI 2010, Beijing, China, September 20, 2010, Revised Selected Papers - Yoshida, Hiroyuki; Cai, Wenli (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the International Workshop on Computational Challenges and Clinical Opportunities in Virtual Colonoscopy and Abdominal Imaging, held in conjunction with MICCAI 2010, in Beijing, China, on September 20, 2010. The 19 revised full papers presented were carefully reviewed and selected from 26 submissions. The papers are organized in topical sections on CT colonography CAD, abdominal imaging, and virtual colonoscopy.